Aos sinais das Ave Marias: furtos de hóstias, feituras de proteção e o desenho religioso da Bahia setecentista: o caso das Diligências de Muritiba - Rangel, Felipe Augusto Barreto (2015)
Studies of magical practices and popular religiosities have revealed important facets of modern miscegenation. The bolsas de mandinga, one of the numerous magic instruments of protection, congregated elements and experiences of social and cultural universes disparate, fruit of religious atlantic dynamics. The processes of comprehension, elaboration and commercialization of these amulets were not as directs and revealed, because of the repressor activities of religious instances, which scoured the Portuguese overseas in search of the devil affronts to Catholic Christianity, made through the variable heterodoxies that drew in overseas. In this sense, we trace as objective to undertake a micro analysis of what we treat, while production of development processes, through documentary information, focusing on the predilection by the insertion of consecrated hosts inside the bolsas de mandinga, attentive, yet, to the motivations, contexts, experiences and understandings of involved subjects. We use a large body of documents, with a clear qualitative option, especially the inquisitorial files. We elected the written narrative in Diligências sobre o caso do desacato e sacrilégio cometido na igreja paroquial de São Pedro do Monte Moritiba, na Baía, concerning the Bahian Reconcavo, in the first half of 18th century, as the backbone of our proposal. Crossed the information present in our sources, through the evidentiary framework proposed by Carlo Ginzburg, and soaked by theoretical proposals of micro studies and trajectories, we seek to understand the religious creolization processes in Bahian Reconcavo eighteenth century. The small fragments collected through the coppery documentary lines show us how the everyday life of investigated subjects measured their spiritual universe, allowing the elaborations, called here Feituras de Proteção.